2014
DOI: 10.1007/s00405-014-3242-9
|View full text |Cite
|
Sign up to set email alerts
|

A new suggestion for the Epworth Sleepiness Scale in obstructive sleep apnea

Abstract: The aim of this study was to suggest a new cutoff score for the Turkish version of Epworth Sleepiness Scale (ESS) in the patients with obstructive sleep apnea. In this study, the data of 483 patients who were admitted to our clinic with the complaints of daytime sleepiness and witnessed sleep apnea were reviewed retrospectively. The correlation between ESS and polysomnography (PSG) findings were assessed, and cutoff score of the Turkish version of the ESS was investigated. The mean apnea-hypopnea index (AHI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…The ESS is used for the evaluation of OSAS patients' complaints of daytime sleepiness. 32 In our study, there was a significant improvement for ESS scores in both groups, and the decrease of ESS scores was statistically similar in both groups.…”
Section: Discussionsupporting
confidence: 71%
“…The ESS is used for the evaluation of OSAS patients' complaints of daytime sleepiness. 32 In our study, there was a significant improvement for ESS scores in both groups, and the decrease of ESS scores was statistically similar in both groups.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have shown some limitations in using the EMS-SI in a survey, such as recall bias and a tendency by respondents to under-report [17]. There were some other limitations in the present study.…”
Section: Limitationsmentioning
confidence: 73%
“…Sleep deprivation can also affect physicians' clinical performance and patient safety, particularly affecting resident physicians [17][18][19][20]. Night shift nurses with sleep deprivation are also more likely to make errors in patient care [21].…”
Section: Introductionmentioning
confidence: 99%
“…Tüm hastaların detaylı anamnezi alındı, Türkçe olarak valide edilmiş EUS uygulandı, gündüz aşırı uykuluğu Kum ve ark. önerdiği şekilde EUS ≥8 olduğunda kaydedildi (8,10). Tüm hastalara nokturnal PSG yapıldı.…”
Section: Gereç Ve Yöntemunclassified